Repeated introduction and spread of the MRSA clone t304/ST6 in northern Europe. (February 2021) - Bartels, M.D.; Worning, P.; Andersen, L.P.; Bes, M.; Enger, H.; Ås, C.G.; Hansen, T.A.; Holzknecht, B.J.; Larssen, K.W.; Laurent, F.; Mäkitalo, B.; Pichon, B.; et al.
Abstract: Objectives: During the last decades several methicillin-resistant Staphylococcus aureus (MRSA) clones with the capability of global spread have emerged in the community. Here, we have investigated a large collection of clinical isolates belonging to MRSA clone t304/ST6, which has emerged in many European countries over the last years, in order to retrace its phylogeny and its spread. Methods: We characterized 466 ST6 isolates from Denmark ( n  = 354), France ( n  = 10), Norway ( n  = 24), Sweden ( n  = 27) and the UK ( n  = 51). All had spa -type t304 ( n  = 454) or t304-related spa -types ( n  = 12) and whole genome sequencing (WGS) was carried out on Illumina Miseq or Hiseq with 100–300 bp reads. cgMLST was performed using Ridom SeqSphere. Results: A minimum spanning tree (MST) of all 466 isolates showed one large cluster including 182 isolates collected only from Denmark and related to a long-term neonatal outbreak in Copenhagen. This cluster contrasted with numerous small clusters, including the remaining Danish isolates and isolates from the other countries that interspersed throughout the tree. Most isolates were Panton-Valentine leukocidin (PVL) negative (95%) and harboured SCC mec IVa. One genome was closed using Oxford Nanopore technology and Illumina MiSeq. It contained a plasmid of 19.769 bp including the bla Z gene. A similar plasmid was found in 78% of all isolates. Discussion: t304/ST6 is a successful emerging clone and the fact that isolates from five countries are interspersed throughout the MST indicates a common origin. This clone is commonly described in the Middle East and its emergence in Europe coincides with influx of refugees from the Syrian Civil War.